2016
DOI: 10.1155/2016/5958196
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Fibrillation-Induced Cardiac Arrest Results in Regional Cardiac Injury Preferentially in Left Anterior Descending Coronary Artery Territory in Piglet Model

Abstract: Objective. Decreased cardiac function after resuscitation from cardiac arrest (CA) results from global ischemia of the myocardium. In the evolution of postarrest myocardial dysfunction, preferential involvement of any coronary arterial territory is not known. We hypothesized that there is no preferential involvement of any coronary artery during electrical induced ventricular fibrillation (VF) in piglet model. Design. Prospective, randomized controlled study. Methods. 12 piglets were randomized to baseline and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…GLS and GLSR were still impaired 72 h post-ROSC and less so at 96 h; this can be at least partly attributed to later recovery of the IVS and lateral wall since regional abnormalities were identified ( Figure 5 ; see Supplementary data online , Table S2 ). To our knowledge, only one previous study 22 reported in a VF CA model in piglets studied with magnetic resonance imaging 4 h post-ROSC regional LV wall motion abnormalities in the territory of the left anterior descendent artery without a difference in myocardial perfusion parameters. As for these authors, we do not know the reasons and the mechanisms of this finding.…”
Section: Discussionmentioning
confidence: 99%
“…GLS and GLSR were still impaired 72 h post-ROSC and less so at 96 h; this can be at least partly attributed to later recovery of the IVS and lateral wall since regional abnormalities were identified ( Figure 5 ; see Supplementary data online , Table S2 ). To our knowledge, only one previous study 22 reported in a VF CA model in piglets studied with magnetic resonance imaging 4 h post-ROSC regional LV wall motion abnormalities in the territory of the left anterior descendent artery without a difference in myocardial perfusion parameters. As for these authors, we do not know the reasons and the mechanisms of this finding.…”
Section: Discussionmentioning
confidence: 99%